Impact of Preoperative Left Ventricular Dysfunction on Surgical Outcomes and Mortality in Patients Undergoing Emergency Abdominal Surgery - Muhammad Hussain, Aamir Siddique, Waqar Ahmed, Naeem Ullah Khan, Waqas Qurshi, Alvina Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Emergency abdominal surgery carries a high risk of morbidity and mortality, particularly in patients with compromised cardiovascular function. Preoperative left ventricular (LV) dysfunction reduces cardiac reserve and may significantly worsen surgical outcomes; however, its impact in emergency settings remains insufficiently studied. Objective: To evaluate the impact of preoperative left ventricular dysfunction on postoperative complications and mortality in patients undergoing emergency abdominal surgery. Methods: This cross-sectional study was conducted from June 2022 to June 2023 at the Department of Cardiology, Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC), Wazirabad, in collaboration with Amna Inayat Medical College. A total of 100 patients undergoing emergency abdominal surgery were included. Preoperative echocardiography was performed to assess left ventricular ejection fraction (LVEF), and patients were categorized into normal (≥50%), mild dysfunction (40–49%), and moderate-to-severe dysfunction (<40%). Postoperative outcomes including complications, ICU admission, hospital stay, and 30-day mortality were recorded. Results: LV dysfunction was present in 37% of patients. Postoperative complications were significantly higher in patients with LV dysfunction compared to those with normal LVEF (67.6% vs. 38.1%, p < 0.001). ICU admission was required in 56.8% of patients with LV dysfunction versus 26.9% in the normal group (p = 0.002), and hospital stay was significantly prolonged (13.1 ± 4.7 vs. 8.9 ± 3.3 days, p < 0.001). The overall mortality rate was 17%, with significantly higher mortality in patients with LV dysfunction (32.4% vs. 7.9%, p = 0.001). Conclusion: Preoperative LV dysfunction is a strong independent predictor of adverse postoperative outcomes and mortality in emergency abdominal surgery. Early cardiac assessment and targeted perioperative management are essential to improve patient outcomes. Keywords: left ventricular dysfunction, emergency abdominal surgery, mortality, ejection fraction, cardiac risk, postoperative complications.